A three-dimensional numerical comparison of bearing capacity and settlement of tapered and under-reamed piles. Issue 3 (4th May 2019) - Vali, Ramin; Mehrinejad Khotbehsara, Elham; Saberian, Mohammad; Li, Jie; Mehrinejad, Mojdeh; Jahandari, Soheil
Abstract: Tapered piles by top cross sections larger than the toe cross sections and under-reamed piles by having one or more bulbs, have the potential for substantial major sides over conventional straight-sided piles. Most of the studies on tapered and under-reamed piles have been conducted on the experimental side, while, theoretical studies, such as finite element method, have been mainly confined to conventional straight-sided piles. On the other hand, although several field, laboratory and experimental studies have been conducted to study the behaviour of tapered and under-reamed piles, few numerical studies have been carried out to simulate the behaviour of the piles. In addition, there is no research to compare and evaluate behaviour of these two piles due to different geotechnical and geometrical properties. Therefore, the aim of this study was to numerically investigate bearing capacity and settlement of tapered and under-reamed piles by changing the soil type, cohesion, angle of internal friction, the length and diameter of piles, tapering degree and the number of bulbs using finite element method. Based on the FEM results, it was found that by increasing the values of geotechnical and geometrical properties, bearing capacity of the tapered pile was more than that of the under-reamed one (i.e. settlement of tapered pile was less than that of the under-reamed one). The reason for this trend could be attributed to increasing contact surface area, friction resistance and more adhesion between soil and the tapered pile. In addition, bulb number of under-reamed piles and tapering degree of tapered piles had significant effects on settlement and bearing capacity of the piles.